2021
DOI: 10.21926/aeer.2104033
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Mobility, Reactivity, and Remediation of Heavy Metal(loid) Pollution: A Review

Abstract: Heavy metal(loid)s are a group of elements present commonly in the environment, including Cr, Ni, Cu, Zn, Cd, Hg, Pb, and As elements, among others. While these elements could have their origins in natural sources, anthropogenic activities, such as mining, agriculture, industry, etc., are also responsible for enhancing the concentration of these elements in the ecosystems up to undesirable levels. A few of these metal(loid)s serve as necessary micronutrients for life, while the others are extremely harmful and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…"Most heavy metals occur naturally, but a few are derived from anthropogenic sources. They are characterized with high atomic mass and toxicity to living organisms" [2]. "Toxicity of heavy metals increases by mixing with different environmental elements, such as water, soil, and air.…”
Section: Introductionmentioning
confidence: 99%
“…"Most heavy metals occur naturally, but a few are derived from anthropogenic sources. They are characterized with high atomic mass and toxicity to living organisms" [2]. "Toxicity of heavy metals increases by mixing with different environmental elements, such as water, soil, and air.…”
Section: Introductionmentioning
confidence: 99%
“…Power generation and transmission are two of the major causes of cancer in humans [12,13]. Reports have shown that power transmission and distribution activities can elevate the concentrations of metals in the environment [14][15][16][17][18]. Metals such as aluminum (Al), copper (Cu), iron (Fe), cadmium (Cd), and lead (Pb) are closely associated with power transmission and distribution, hence, the environment could be contaminated by these metals over time.…”
Section: Introductionmentioning
confidence: 99%
“…The anthropogenic pollution is known as pollution caused by conventional fuels, chemicals, noise, electromagnetic fields and waste pollution [22][23][24]. A third source of atmospheric pollution with heavy metals is the biotic environment, through vegetation, the residues' storage, and manure [25][26][27].…”
Section: Introductionmentioning
confidence: 99%